2018
DOI: 10.1021/acssuschemeng.8b05717
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Oxygen Vacancies into LaCoO3 Perovskite for Efficient Electrocatalytic Oxygen Evolution

Abstract: Oxygen vacancies (OVs) can improve catalytic activities in oxygen evolution reaction (OER). Although considerable effort has been devoted to increasing the OVs concentration in electrocatalysts, limited OVs have been created by current techniques so far. Here, we, for the first time, engineered (i.e., created) abundant OVs into perovskites by element doping and plasma treatment. The results revealed that more OVs were manufactured by combination of Sr doping with Ar plasma treatment, leading to improved OER ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…Among the investigated ionic vacancies, oxygen vacancy has been widely applied to tune electrocatalytic properties due to the low formation energy of this kind of vacancy. [ 100–102,110 ] The previous studies have been proved that the introduced oxygen vacancies could decrease the electrical resistance efficiently and then benefit to enhance the catalytic performance for OER. [ 61a ] Moreover, it is important to elucidate the relationship between oxygen vacancy concentration and electrocatalytic performance for the design of efficient electrocatalysts.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…Among the investigated ionic vacancies, oxygen vacancy has been widely applied to tune electrocatalytic properties due to the low formation energy of this kind of vacancy. [ 100–102,110 ] The previous studies have been proved that the introduced oxygen vacancies could decrease the electrical resistance efficiently and then benefit to enhance the catalytic performance for OER. [ 61a ] Moreover, it is important to elucidate the relationship between oxygen vacancy concentration and electrocatalytic performance for the design of efficient electrocatalysts.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…Perovskite oxides (ABO 3 ), which incorporate rare‐earth cations (A‐site) and transition metal cations (B‐site), have been recognized as potential alternatives noble‐metal electrocatalysts owing to its high ionic and structure flexibility . In previous studies, LaCoO 3 (LCO) was found to be a durable and active OER catalyst . Theoretical studies anticipated that the OER activity of the perovskite depends on the electronic structure of the transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…[ 96 ] Recently, the importance of OVs in perovskite oxide electrocatalysts was also addressed, [ 28 ] which act as active sites and hence improve intrinsic activity. [ 97 ] Mefford et al. substituted La 2+ with Sr 2+ in LaCoO 3 and investigated the influence of OVs and BO bond covalency on the electrocatalytic performance.…”
Section: Characterization Of Vacanciesmentioning
confidence: 99%